The Maternal Early Warning Criteria. Issue 3 (September 2015) - Mhyre, J.M.; D'Oria, R.; Hameed, A.B.; Lappen, J.R.; Holley, S.L.; Hunter, S.K.; Jones, R.L.; King, J.C.; D'Alton, M.E.
<x xml:space="preserve">Abstract</x> (Obstet Gynecol. 2014;124(4):782–786)